2009
DOI: 10.1002/jat.1440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic concentration–time response in A549 cells exposed to respirable α‐quartz

Abstract: A causal pathway between quartz, silicosis and lung cancer has been postulated. The aim of our study was to assess cytotoxic effects induced in a human lung epithelial cell line (A549) by exposure to alpha-quartz. Cells were exposed to respirable alpha-quartz (SRM1878a, NIST) at 25, 50 or 100 microg ml(-1 )for 24 h and at 50 or 100 microg ml(-1) for 48 h. Cytotoxic effects were analyzed by scanning electron microscopy (SEM), apoptotic morphology analysis with Hoechst staining and lactate dehydrogenase (LDH) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…But whether elevated TGFβ is also a potent inducer for Egr-1 in this process, in other word whether there is an Egr-1 /TGFβ positive feedback loop need to be further explored. Many studies found silica induced cell apoptosis [38,39], and recent studies [40,41] demonstrated that Egr-1 took part in regulating cell apoptosis, but whether activated Egr-1 plays an important role in silicosis by affecting cell apoptosis need further study to elucidate.…”
Section: Discussionmentioning
confidence: 99%
“…But whether elevated TGFβ is also a potent inducer for Egr-1 in this process, in other word whether there is an Egr-1 /TGFβ positive feedback loop need to be further explored. Many studies found silica induced cell apoptosis [38,39], and recent studies [40,41] demonstrated that Egr-1 took part in regulating cell apoptosis, but whether activated Egr-1 plays an important role in silicosis by affecting cell apoptosis need further study to elucidate.…”
Section: Discussionmentioning
confidence: 99%
“…SEM and TEM photographs of these cells were taken using ordinary methods, and various cell protrusions or microvilli were reported (Fanizza et al, 2009;Gualtieri et al, 2005;Ishigaki et al, 2011a;Wang et al, 2009). Rose Wrap, a food film wrap (C.I.…”
Section: Methodsmentioning
confidence: 99%
“…Such features were also observed in cultured cells by SEM and atomic microforce microscopy (Braet et al, 1998; Kim et al, 2008; Solmi et al, 2008). Although other researchers have previously observed microvilli in A549 cells (Fanizza et al, 2009; Gualtieri et al, 2005; Wang et al, 2009), to our knowledge, this is the first observation of cell‐to‐cell connections among A549 cells under an electron microscope.…”
Section: Resultsmentioning
confidence: 45%
“…SEM and transmission electron microscopy (TEM) micrographs of A549 cells have been reported by other researchers (Fanizza et al, 2009; Gualtieri et al, 2005; Wang et al, 2009). Similar to those images, SEM images of the platinum‐coated A549 cells taken in this study also showed flat shapes adhering to the polymer sheet.…”
Section: Resultsmentioning
confidence: 54%